A radioanatomic study of the internal mammary artery and its perforators using multidetector computed tomography angiography. Issue 4 (18th September 2013) - Tan, Onder; Yuce, Ihsan; Aydin, Osman Enver; Kantarci, Mecit
<x xml:space="preserve">Abstract</x> The Internal Mammary Artery (IMA) and its perforators play an important role in coronary bypass grafting and reconstructive breast, head, and neck surgery. This study aimed to obtain anatomic data pertaining to these vessels using Multi Detector Computed Tomography Angiography (MDCTA) and to demonstrate that the MDCTA could be a considerable assessment tool prior to surgery. In 50 outpatients (27 males and 23 females), the above‐mentioned arteries were bilaterally evaluated with a 16‐detector spiral computed tomography scanner. Based on the obtained images, diameters of the bilateral IMAs were separately measured in each intercostal spaces from 1 to 5 through their traces. IMAPs greater than 0.5 mm in diameter were bilaterally evaluated in terms of distance from the sternal border to the ramification point under the muscular layer, maximal external diameter at ramification from the IMA, and the length between the ramification point from the IMA and enter point to the subcutaneous fat tissue. Mean diameters of the left and right IMAs were 2.05 ± 0.50 mm and 2.20 ± 0.57 mm, respectively. Mean diameters, distances, and lengths of the perforators were 1.30 ± 0.30 mm, 6.80 ± 3.40 mm, 17.05 ± 6.07 mm on the left side and 1.32 ± 0.25 mm, 6.71 ± 3.43 mm, 17.35 ± 3.48 mm on the right side, respectively. No statistically difference was found between the sides (P > 0.05). About 20 of 36 perforators appeared in the second intercostal space, whereas there were eight in the first and eight in the third intercostal space. MDCTA, as a non‐invasive vascular imaging method, can be a valuable tool for investigating the anatomic characteristics of the IMA and its perforators before planning an operation. © 2013 Wiley Periodicals, Inc. Microsurgery 34:277–282, 2014.